2010
DOI: 10.1111/j.1469-8137.2010.03398.x
|View full text |Cite
|
Sign up to set email alerts
|

Disjunct distribution of chloroplast DNA haplotypes in the understory perennial Veratrum album ssp. oxysepalum (Melanthiaceae) in Japan as a result of ancient introgression

Abstract: Summary• The Quaternary climatic changes resulted in range shifts of species, providing chances for hybridization. However, the genetic signatures of such ancient introgression have rarely been reported. To investigate such signatures, we performed a phylogeographical study on the perennial plant Veratrum album ssp. oxysepalum, which may have hybridized long ago with another congeneric species, V. stamineum.• Sequence variations in chloroplast DNA (cpDNA) were examined in 43 populations in Japan and adjacent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 82 publications
4
63
0
Order By: Relevance
“…Schluter 2009; Schemske 2010) and partly concur with the limited number of empirical studies involving one or two similar genetic markers in plants (e.g. Bai et al 2010;Kikuchi et al 2010;Mims et al 2010;Wang et al 2011a). …”
Section: Discussionmentioning
confidence: 78%
“…Schluter 2009; Schemske 2010) and partly concur with the limited number of empirical studies involving one or two similar genetic markers in plants (e.g. Bai et al 2010;Kikuchi et al 2010;Mims et al 2010;Wang et al 2011a). …”
Section: Discussionmentioning
confidence: 78%
“…J5; Figures 1a and 3), is strongly suggestive of a two-refugia scenario and a narrow contact zone between the two lineages. Interestingly, this putative contact region coincides with a well-known inter- and intraspecific suture zone of Japan’s temperate flora and fauna [14,108,109,12]. On the other hand, the Tpi data are more consistent with a multiple-refugia scenario, that is, haplotypes are largely restricted to particular (sub)regions and/or populations, while still showing a relatively small amount of shared polymorphisms, mainly (but not exclusively) among adjacent sites (Figure 2a).…”
Section: Discussionmentioning
confidence: 85%
“…Abaso ( Figure 1 ). Given that biparentally inherited nuclear gene loci are more effective for species delimitation than maternally inherited ptDNA markers in many angiosperm genera (Bai et al, 2010; Kikuchi et al, 2010), and the extant P. mexicana species are morphologically distinct and reproductively isolated from other NA species (Eckenwalder, 1996a), it is quite reasonable that P. mexicana would form its own section. In addition, the placement of P. mexicana in a basal position of the genus Populus , which is consistent with Eckenwalder’s interpretation based on morphological traits, the leaf morphology of extant P. mexicana was similar to the oldest poplar fossil from the Eocene (Manchester et al, 1986) together suggested that section Abaso may be an ancestral lineage.…”
Section: Discussionmentioning
confidence: 99%